Amar Makruf Nahi Munkar Muâ€˜tazilah dalam Perspektif al-ZamakhsharÃ® - Muhibbin, Zainul (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
Islamic command on Amar Makruf Nahi Munkar has been basically intended for all Muslims regardless of their theological affiliation. Mu?tazila, however, has a typical understanding of it. Al-Zamakhsharî, as one of Mu?tazilites clerics and mufassir, who wrote al-Kashshâf, discusses the concept of Amar Makruf Nahi Munkar together with its contextual meaning. This problem is investigated and analyzed by using descriptive methodology, content analysis and contextual analysis. From the data collected and analysis conducted it is concluded that Amar Makruf Nahi Munkar in al-Zamakhsharî?s perspective is considered wajib kifayah in a sense that it should be in accordance with the capacity and competence of its doers, with the method of treatment ranging from soft to firm action, even with fight whenever necessary to do so. In the present context, al-Zamakhsharî?s perspective on Amar Makruf Nahi Munkar has turned out to be relevant to be implemented in more actual. The appeal applies to all levels, from the Government, the ulama and intellectuals to the common people.